2017
DOI: 10.1111/scs.12435
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, coping strategies, social support and self‐efficacy in women after acute myocardial infarction: a mixed methods approach

Abstract: Background Quality of life, coping strategies, social support and self‐efficacy are important psychosocial variables strongly affecting the experience of acute myocardial infarction (AMI) in women. Aims To gain a more in‐depth understanding of how coping strategies, self‐efficacy, quality of life and social support shape women's adjustment to AMI. Design Mixed methods study. Quantitative data were collected through a standardised questionnaire on coping strategies, self‐efficacy, quality of life and social sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Psychological factors were the most frequently studied variables in women who had experienced an ACS, with women experiencing both positive and negative effects (Bergman et al., 2011; Fuochi & Foa, 2017; Mendes et al., 2010; Norekval et al., 2008; Shin et al., 2010; Weislander et al., 2016) . Data collection methods were primarily based on semi‐structured face to face interviews and self‐reported questionnaires such as sense of coherence (SOC) scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological factors were the most frequently studied variables in women who had experienced an ACS, with women experiencing both positive and negative effects (Bergman et al., 2011; Fuochi & Foa, 2017; Mendes et al., 2010; Norekval et al., 2008; Shin et al., 2010; Weislander et al., 2016) . Data collection methods were primarily based on semi‐structured face to face interviews and self‐reported questionnaires such as sense of coherence (SOC) scale.…”
Section: Resultsmentioning
confidence: 99%
“…Data collection methods were primarily based on semi‐structured face to face interviews and self‐reported questionnaires such as sense of coherence (SOC) scale. The sample sizes varied between 12 (Mendes et al., 2010) and 250 (Fuochi & Foa, 2017; mean age of 72 years old). Changes in psychological state of women were often individualized and related to their personal attitudes and attributes (Norekval et al., 2010; Weislander et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This method is very much in its infancy in neurology research and has been used to investigate single issues ( 97 100 ), caregiver’s burden ( 101 , 102 ), and prospective studies ( 103 , 104 ). It is outside the field of neurology where it has been shown to be effective in assessing the more global issue of HQoL ( 105 , 106 ). Our work is paradigmatic of a mixed-methodology approach that holds huge potential for in-depth investigation of HQoL issues in chronic neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the SSE and CWSE domains and the total RTWSE score were able to predict overall job satisfaction (AUC 0.70). The impact of job satisfaction scores on work-related compensation status and recovery has been well documented, 22,31,[31][32][33] and the positive association between satisfaction and the RTWSE was anticipated. Low SSE and CWSE scores reveal suboptimal satisfaction with the support received at work and may assist in identifying workers with negative outcomes or unsustainable RTW efforts.…”
Section: Cross-sectional Known-groups Validitymentioning
confidence: 95%
“…Previous research has shown that self-efficacy is associated significantly and negatively with pain-related disability in patients with chronic pain. [28][29][30] These studies however, have not reported the strength of association and have based their findings on statistical significance. ; AUC values were calculated for 2 satisfaction categories (satisfied and neutral, dissatisfied).…”
Section: Construct Convergent Validitymentioning
confidence: 99%